Surface spin asymmetry in Pt(001)–hex induced by electron accumulation - Larisa E Borcan; Cristian M Teodorescu; Alexandru-Cristi Iancu; Nicoleta G Apostol; Adela Nicolaev; Ruxandra M Costescu; Marius A Hușanu; Dana G Popescu; George A Lungu; Marco Bianchi (JPhys Materials, 2025)
Spin asymmetry is detected in clean Pt(001)– hex by spin-resolved photoelectron spectroscopy even in absence of external sample magnetization. Magnetization of the sample immediately after preparation yields a consistent remnant spin asymmetry in the direction of the applied magnetic field. The surfaces were also characterized by low energy electron diffraction, scanning tunneling microscopy and high resolution core level x-ray photoelectron spectroscopy, allowing one to quantify the surface component, attributed to the last surface layer enriched in electrons. The explanation of the spin asymmetry induced by electron accumulation into the last monolayer is sketched by using band ferromagnetism criteria. The orientation of the spin asymmetry in the nonmagnetized sample coincides with the direction of the rows of the hex reconstruction, while in the magnetized sample it is aligned with the direction of the external magnetizing field. A strong variation of the spin asymmetry as function of the binding energy near the Fermi level, whose amplitude depends also on the median emission angle, suggests a spin textured state in this energy range or the presence of a Stoner gap.